Carnival Under Surveillance: Sultan Tolba and The Politics of French Colonial Governance - Bekkaoui, Salaleddine (International Journal of Language and Literary Studies, 2026)
This article examines Sultan Tolba, the spring festival organised annually by the madrasa students (tolba) of Fez, focusing on its historical origins, ritual stages, and political meanings. Based on a historical approach combining archival research with analysis of colonial and Moroccan sources, it argues that under the French Protectorate (1912–1956) the ritual was not simply tolerated but actively appropriated and managed by colonial authorities. Protectorate officials inserted themselves into the festival’s ceremonial economy through monetary gifts (mouna/hadiya), official visits, translated speeches, photographic staging, and the careful reproduction of makhzenian protocol in colonial performance. Drawing on colonial reports (including the Bulletin Officiel), eyewitness testimony such as that of Louis de Barthou, and interpretations of ritual discourse by scholars such as Jocelyne Dakhlia, the article demonstrates how colonial governance sought to domesticate the festival’s inherent ambivalence by transforming licensed inversion into a supervised spectacle—at once an instrument of pacification and a site where anxieties about student mobilisation remained visible. Sultan Tolba thus reveals how colonial power governed through ritual continuity, converting parody into political pedagogy and symbolic inversion into a reaffirmation of sovereign order. At the same time, drawing on postcolonial theory—particularly Homi Bhabha’s concept of ambivalence and Mikhail Bakhtin’s notion of the carnivalesque—the article shows how the tolba, while appearing to reproduce the ritualised spectacle of colonial authority, subtly destabilised its symbolic structures from within.